Elevated Monocyte Chemoattractant Protein-1 and Nuclear Factor Kappa B Biomarkers in Captagon and Methamphetamine Addiction - Mahmood Mehdi Rasheed; Hassan Ali Al-Saadi; Amer Alhaideri (Karbala Journal of Medicine, 2025)
Background: Addiction is a complex, chronic brain disorder characterized by compulsive drug seeking and use despite harmful consequences. They affect approximately 10% of the population, and this percentage increases over time. This study aimed to investigate the roles of monocyte chemoattractant protein-1 (MCP-1) and nuclear factor kappa B (NF-κB) in patients addicted to captagon and methamphetamine. Methods: This case-control study was carried out for addicted patients with captagon and methamphetamine at the Rehabilitation Center for Drug and Substance Abusers in the Directorate of Narcotics and Psychotropic Substances in the Karbala governorate from November 2024 to May 2025. Results: White blood cell (WBC) levels decreased for both unmarried and married patients, while red blood cells (RBC) decreased in unmarried patients. Hematocrit test (HCT), mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH) values increased significantly in both unmarried and married patients with captagon and methamphetamine users compared with healthy individuals. MCP-1 was elevated in married captagon users (470.67 ± 258.41 pg/mL; p < 0.00001) and unmarried methamphetamine users (459.40 ± 151.30 pg/mL; p < 0.00001). NF-κB was elevated across all user groups (p < 0.00001). Receiver operating characteristic (ROC) analysis for MCP-1 (AUC = 99.235%; sensitivity 97.778%, specificity 97.778%) and NF-κB (AUC = 96.716%; sensitivity 94.444%, specificity 95.556%) showed excellent diagnostic accuracy. Conclusions: MCP-1 levels were higher in married captagon users than in unmarried captagon users, whereas unmarried methamphetamine users exhibited higher MCP-1 than married methamphetamine users. NF-κB levels were markedly higher in both unmarried and married captagon and methamphetamine users.